2014
DOI: 10.4103/0019-5154.135525
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between alopecia areata and alexithymia, anxiety and depression: A case-control study

Abstract: Background:Alopecia areata (AA) is a skin disease characterized by the sudden appearance of areas of hair loss on the scalp and other hair-bearing areas, but its aesthetic repercussions can lead to profound changes in patient's psychological status and relationships.Aim:The goal was to investigate a possible relationship between AA and alexithymia as well as two other emotional dimensions, anxiety and depression.Materials and Methods:Fifty patients with AA seen in the Department of Dermatology of Hedi Chaker U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
79
1
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(104 citation statements)
references
References 38 publications
8
79
1
16
Order By: Relevance
“…In accordance with previous studies, women with AA had significantly more psychological problems, especially somatization, anxiety and hostility, in the present study. This has been attributed to a higher degree of AA‐related distress in women than in men, probably because hair plays a more important role in their self‐image and self‐esteem, because they are more sensitive to hair loss, and because hair loss is more difficult to accept, leading to anxiety reactions …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with previous studies, women with AA had significantly more psychological problems, especially somatization, anxiety and hostility, in the present study. This has been attributed to a higher degree of AA‐related distress in women than in men, probably because hair plays a more important role in their self‐image and self‐esteem, because they are more sensitive to hair loss, and because hair loss is more difficult to accept, leading to anxiety reactions …”
Section: Discussionsupporting
confidence: 93%
“…This has been attributed to a higher degree of AA-related distress in women than in men, probably because hair plays a more important role in their self-image and self-esteem, because they are more sensitive to hair loss, and because hair loss is more difficult to accept, leading to anxiety reactions. 11,[32][33][34] We also found that there was a significant correlation between AA duration and psychological distress; furthermore, patients with alopecia totalis or alopecia universalis exhibited higher anxiety and phobic anxiety scores. One possible explanation could be that such patients have more fully realized the potential negative implications of their disease, but have not yet acquired the necessary coping skills.…”
Section: Discussionsupporting
confidence: 56%
“…No association has been found between alexithymia and either acne or seborrhoeic dermatitis . The association between alexithymia and alopecia areata is controversial . Several single‐centre studies have shown that alexithymia is more prevalent among those with psoriasis than in aged‐matched controls from the general population …”
mentioning
confidence: 99%
“…11 The association between alexithymia and alopecia areata is controversial. [12][13][14] Several single-centre studies have shown that alexithymia is more prevalent among those with psoriasis than in aged-matched controls from the general population. [15][16][17][18][19] Information on the prevalence of alexithymia with psoriasis and the association between alexithymia and psoriasis burden is limited.…”
mentioning
confidence: 99%
“…La ansiedad fue responsable de 14,7% de la variación en la alexitimia (P = 0,047). Con esto podemos concluir que existe una alta prevalencia de síntomas de ansiedad y depresión entre los pacientes que sufren una alopecia areata [30].…”
Section: Tipo De Alopecia Y Evolución Clínicaunclassified